The Brightness of Multidisciplinary Approaches in Health Sciences Research - Cortes, Arthur R. G. (2024)
On behalf of the Editorial Team of Scientific Letters journal, we are pleased to announce the publication of the second issue. The second issue comprises four scientific papers, encompassing two reviews and two research articles. In 2023, Scientific Letters also published two special issues in the form of Books of Abstracts. These publications compile all abstracts that were accepted for presentation at the II TOXRUN International Congress and the II UNIPRO International Congress, both held in Portugal. We intend to add “Clinical Case Studies” and “Commentaries” to the list of article types that the journal publishes. We hope you enjoy reading this second issue and find these articles useful for your research. We invite you to submit your best papers for publication.